Penalties, Manipulation, and Investment Efficiency - Nan, Lin; Wen, Xiaoyan (Management Science, 2019)
In this study, we examine whether imposing a penalty based on an earlier positive signal and a bad realized outcome can be welfare-improving. We find that imposing a penalty helps to improve investment efficiency, but it also brings a deadweight cost of potential penalty for entrepreneurs with good projects. We show that when a good project has a much larger chance to achieve a good outcome than a bad project or when a large proportion of the penalty can be reimbursed to the investor, it is optimal to impose a penalty to deter entrepreneurs with bad projects from reporting positive signals to the greatest degree, as the benefit from reducing the investment inefficiency outweighs the expected deadweight cost. Otherwise, it is optimal not to impose any penalty. We also find that a larger penalty may induce more manipulation by a good entrepreneur. This is because, although a larger penalty directly discourages manipulation for both good and bad types by increasing the expected penalty cost, it also encourages upward manipulation by lowering the implicit financing cost upon a high signal. The encouraging effect is mostly pronounced for the good entrepreneur when the good entrepreneur has a much larger chance of success than the bad entrepreneur or when the reimbursement proportion is very high. This paper was accepted by Shiva Rajgopal, accounting.